1998
DOI: 10.1007/s005200050142
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, depression and quality of life in cancer patients: how are they related?

Abstract: In a study concerning a group of cancer patients undergoing radiotherapy three research questions were addressed. (1) Is fatigue a valid criterion for depression in these somatically ill patients? (2) What is the 'cause-andeffect' relation between fatigue and depression? (3) To what extent are fatigue and depression related to patients' quality of life. A heterogeneous sample of cancer patients (n p 250) were interviewed before treatment, 2 weeks after treatment and 9 months later. Fatigue was measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
206
2
16

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(234 citation statements)
references
References 21 publications
10
206
2
16
Order By: Relevance
“…25 QOL studies have found few prostate treatment variables associated with depression. 26 Rather, major findings from these studies indicate that being older, being married, having high social support, being optimistic and having less impairment in physical functioning are associated with decreased risk of depression. 27 --30 The profile of risk factors associated with depression in men with prostate cancer is highly consistent with the profile of factors empirically shown to be associated with risk of depression in general cancer populations.…”
Section: Depression and Prostate Cancermentioning
confidence: 85%
“…25 QOL studies have found few prostate treatment variables associated with depression. 26 Rather, major findings from these studies indicate that being older, being married, having high social support, being optimistic and having less impairment in physical functioning are associated with decreased risk of depression. 27 --30 The profile of risk factors associated with depression in men with prostate cancer is highly consistent with the profile of factors empirically shown to be associated with risk of depression in general cancer populations.…”
Section: Depression and Prostate Cancermentioning
confidence: 85%
“…A relation between fatigue and low QOL has also been reported for other groups of cancer patients. 45 Ovarian carcinoma patients with fatigue also differ from nonfatigue patients in several other respects, with the former showing more anxiety and depression as well as an increased helpless coping behavior. In addition, this group reported significantly lower social support and higher social stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although many cancer studies have examined fatigue during and after chemotherapy, only a small number evaluated fatigue before chemotherapy. These studies found that younger age, female gender, presence of metastases, sleep problems, mood disturbance, lower cognitive function, and poorer performance were all associated with more severe pretreatment fatigue among cancer patients [16,26,34,43]. Studies examining the relationship between sleep and fatigue have primarily found that, during chemotherapy, the two are associated.…”
Section: Introductionmentioning
confidence: 99%
“…Miaskowski and Lee [32], in a study of patients with bone metastasis, found that these patients reported only moderate fatigue but significant sleep disturbance. Several investigators found that fatigue was also related to depression, anxiety, and/or pain in patients undergoing chemotherapy [36,43] and after the end of chemotherapy [9,43]. Three studies examined the relationship between fatigue and reports of sleep disruption before treatment [16,26,34], but no studies examined fatigue and objectively recorded sleep before treatment.…”
Section: Introductionmentioning
confidence: 99%